Kyrgyz Republic : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper identifies constraints to economic growth in the Kyrgyz Republic, using the Hausmann-Velasco-Rodrik diagnostic approach. It finds that large infrastructure gaps, weak governance and rule of law, and high cost of finance appear to be the most binding constraints to private investment and growth. Additional critical factors are the quality of education and onerous regulations. There is room to improve both the quality and cost/efficiency of education spending. Although relatively low, labor costs have exceeded productivity growth and there is room to improve labor market efficiency. Despite important investments, the infrastructure gap remains large and the country ranks relatively low on infrastructure quality. Weak governance undermines growth through various channels: investment, human capital, and productivity. Weak institutions increase the cost of doing business and make the appropriation of investment returns less certain, overall reducing investor's risk appetite to invest. Public debt is on the high side and the composition of spending is tilted toward current spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet